Differences in thermal balance, body temperature and activity between non-melanic and melanic two-spot ladybird beetles (Adalia bipunctata) under controlled conditions - de Jong, P.W.; Gussekloo, S.W.S.; Brakefield, P.M. (Company of Biologists Ltd, 1996)
The consequences of the elytral colour difference between non-melanic (red) and melanic (black) two-spot ladybirds for their thermal properties were studied by applying and testing a biophysical model. The expected differential effects of variation in transmission through the elytra, body size, width of the subelytral cavity, ambient temperature, radiation intensity and wind speed are described, assuming that the two colour patterns represent differences in elytral reflectance and transmittance. The model predicts a higher body temperature for melanic beetles under most conditions. Invasive temperature measurements on living beetles under ranges of specified conditions with respect to ambient temperature, radiative regime and wind speed were in qualitative agreement with the model predictions and, considering the assumptions made, closely corresponded at the quantitative level. The consequences of the temperature differences for morph activity were studied by measuri ng walking speeds and the time needed to become active for each morph under the various conditions. The results are consistent with the differences in body temperature, assuming an optimum curve relating performance to body temperature. The colour difference between morphs appeared to be the principal factor influencing activity.